Tingkat Suku Bunga, Jangka Waktu, Jenis Kredit dan Kredit Macet - Maharani, Ni Luh Putu Eka Putri; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
Bad credit is a condition where credit customers are unable to pay the credit they have on time. This research aims to determine the effect of interest rates, credit terms and types of credit on bad credit. This research was conducted at the Village Credit Institution (LPD) Sukawati District. The sampling method used non-probability sampling and purposive sampling techniques with a total of 88 respondents. The data collection technique uses questionnaires and the data analysis technique uses multiple linear regression analysis techniques. The research results show that the interest rate, credit term and type of credit have a positive and significant effect on bad credit. Keywords: Bad Credit; Interest Rates; Credit Term; Types of Credit